Creative Media Marketing of Food & Beverage and Housekeeping Experiences: Enhancing Guest Engagement and Brand Loyalty in Hotels. - Jain , Shital; Pandirkar , Ajinkya; Kottayi, Amith; Pathan, Imran; Giri, Rupesh; Vichare, Mitesh (Journal of Neonatal Surgery, 2025)
Imaginative media marketing is emerging as a significant strategy tool within the hospitality industry as influencing experiences, and brand loyalty by the hospitality industries guests. This paper explains how the new media marketing idea can be applied to promote the Food and Beverage (F&B) and Housekeeping services that come along with the hotels to enhance their interactions and fulfill their customers. Hotels can be able to create experience of a memorable service through digitalization, social media marketing, and immersion by content marketing, satisfying the expectations of the guests and enhancing emotional connections between them and the mark. The structured questionnaires and interviews are used to collect the primary data in the study, which consist of the combination of primary data collected in the study and the secondary data found in industry reports, windows and books. The findings have shown that creative media marketing contributes significantly to the point of view of guests regarding quality of treatment and level of interest, as well as, whether they would be willing to remain loyal to the guest. The study has practical implications to hotel managers on the best way of leveraging the use of technology, stories and active media in making the experience of customers in F&B and housekeeping segment as rich as possible.